Factors associated with acute depressive symptoms in patients with comorbid depression attending cardiac rehabilitation - Sever, Serdar (BMC Cardiovasc Disord, 2018)
BACKGROUND: The literature suggests that comorbid depression, defined in this paper as a history of depression prior to a cardiovascular event, has an impact on later onset depression as well as constituting increased risk of mortality and adverse cardiac events. However, which factors are associated with depression, specifically in patients with comorbid depression, is unclear. Therefore, this paper investigates the factors associated with depression in patients with comorbid depression attending cardiac rehabilitation (CR). METHODS: This observational study used routinely collected data from the British Heart Foundation National Audit of Cardiac Rehabilitation for the time period between April 2012 and March 2017. CR participants with comorbid depression were selected as the study population. An independent t-test and chi-square test were used to compare the association between acute depression symptoms and baseline characteristics in this population. RESULTS: A total of 2715 CR patients with comorbid depression were analysed. Characteristics associated with acute depressive symptoms in patients with comorbid depression were found to be: young age (MD: 2.71, 95% CI 1.91, 3.50), increased number of comorbidities (MD: -0.50, 95% CI -0.66, − 0.34), increased weight (MD: -1.94, 95% CI -3.35, − 0.52), high BMI (MD: -1.94, 95% CI -3.35, − 0.52), HADS anxiety (MD: -5.17, 95% CI -5.47, − 4.87), comorbid anxiety (52.4%, p <  0.001), physical inactivity (150 min moderate physical activity a week and 75 min vigorous exercise a week; 27.5%, p <  0.001; 5.6%, p <  0.001 respectively), smoking (12.7%, p <  0.001), and being less likely to be partnered (63.6%, p <  0.001). CONCLUSION: The study demonstrated the association between a variety of clinical and socio-demographic factors and depression. The findings of the research indicated that, at CR baseline assessment, caution must be taken with patients with comorbid depression, specifically those with higher level depressive symptoms at the start of rehabilitation. Furthermore, their multi-comorbid condition must also be taken into account. Patients with higher depression symptoms and comorbid depression scored five points higher on the HADS anxiety scale in comparison to patients with lower level depression symptoms at the start of CR, which demonstrated that anxiety and depression are interrelated and present together.